Pengembangan Sistem Informasi Manajemen Bahan Baku Makanan dan Penggajian Karyawan Berbasis Website Menggunakan Metode Extreme Programming - Muhammad Rosyid Ridho; Nur Fajri Azhar; Tegar Palyus Fiqar (LPPM ITK, 2022)
Kanas Kitchen Store is one of the shops engaged in the food and beverage sector located in the city of Balikpapan. Currently, all the processes of collecting raw materials and employee payroll are still recorded manually which results in delays in recording. Therefore, this study proposes the Development of a Website-Based Food Raw Material Management and Payroll Information System. Development of raw material management and payroll information systems for employees using the Laravel framework and MySQL databases, and implementing the Extreme Programming method. The stages in Extreme Programming start from planning, designing, coding, and testing. There are several features in this study, namely, raw material features, employee attendance features, and employee payroll features. In the implementation of the design of the raw material management information system and employee payroll, user stories were obtained from the results of interviews with the needs of the system totaling 35 user stories, then continued in designing database designs and use case diagrams. In completing the development of the website information system raw material management and employee payroll with a total of 35 user stories and implemented as many as 5 iterations. The extreme programming method can be implemented in research on the development of raw material management systems and employee payroll. The results of the research on the application of the Food Raw Material Management Information System and Employee Payroll are proven by the results of testing with the unit testing method and can be carried out in accordance with meeting the user acceptance test.